Work-Related Open-Globe Injuries: Demographics and Clinical Characteristics. Issue 2 (March 2013) - Bauza, Alain M.; Emami, Parisa; Son, Jung H.; Langer, Paul; Zarbin, Marco; Bhagat, Neelakshi
Purpose: To describe the demographics and clinical characteristics of work-related open-globe injuries (OGIs) at a level I trauma center over a 10-year period. Methods: Retrospective series. Results: A total of 183 eyes with work-related OGIs were identified. The majority of injuries occurred in men (96.7%). The anatomic site of the wound was zone 1 in 107 eyes (72.3%). The most common cause was nail gun use (47.0%). The types of OGI included 32 ruptures (17.5%), 112 penetrating injuries (61.2%), 38 intraocular foreign bodies (IOFB) (20.8%), and 1 mixed rupture/IOFB injury (0.5%). Presenting visual acuity (VA) was worse than 20/200 in 112 eyes (65.9%) and no light perception (NLP) in 10 eyes (5.8%). Final VA worse than 20/200 occurred in 64 eyes (37.2%); 11 eyes underwent enucleation. In comparison to non-work-related OGIs (420 eyes), we found significant differences in types and zones of injury, initial and final mean VA, enucleation rate, incidence of cataracts, hyphema, retinal detachment, hemorrhagic choroidals, and afferent pupillary defect (APD). Using multivariate analysis, significant prognostic factors for a final VA of NLP were zone 3 injury, rupture injury, and initial VA of NLP. Risk factors for enucleation included zone 3 injury, APD, and endophthalmitis. Conclusions: Work-related injuries were noted to have a much higher incidence of IOFBs and cataracts compared to non-work-related OGIs. Zone 3 injuries, rupture injuries, and a presenting VA of NLP were found to be significant predictors for a final VA of NLP. Zone 3 injury, APD, and endophthalmitis were found to be significant predictors for enucleation.